Effect of the addition of nano-sized sodium hexametaphosphate to fluoride toothpastes on tooth demineralization: an in vitro study - Dalpasquale, Giovanna [UNESP]; Delbem, Alberto Carlos Botazzo [UNESP]; Pessan, Juliano Pelim [UNESP]; Nunes, Gabriel Pereira [UNESP]; Gorup, Luiz Fernando; Neto, Francisco Nunes Souza; de Camargo, Emerson Rodrigues; Danelon, Marcelle [UNESP] (Springer Nature, 2017)
Objective: This study evaluated the effect of toothpastes containing 1100 ppm F associated with nano-sized sodium hexametaphosphate (HMPnano) on enamel demineralization in vitro using a pH-cycling model. Design: Bovine enamel blocks (4 mm × 4 mm, n = 72) selected by initial surface hardness (SHi) were randomly allocated into six groups (n = 12), according to the test toothpastes: without fluoride or HMPnano (Placebo), 550 ppm F (550F), 1100 ppm F (1100F), 1100F plus HMPnano at concentrations of 0.25% (1100F/0.25%HMPnano), 0.5% (1100F/0.5%HMPnano), and 1.0% (1100F/1.0%HMPnano). Blocks were treated 2×/day with slurries of toothpastes and submitted to five pH cycles (demineralizing/remineralizing solutions) at 37 °C. Next, final surface hardness (SHf), integrated loss subsurface hardness (ΔKHN), integrated mineral loss (gHAp × cm−3), and enamel fluoride (F) concentrations were determined. Data were analyzed by ANOVA and Student-Newman-Keuls test (p < 0.001). Results: Toothpaste with 1100F/0.5%HMPnano led to the lowest mineral loss and the highest mineral concentration among all groups, which were 26% (SHf) and 21% (ΔKHN) lower and ~58% higher (gHAp × cm−3) when compared to 1100F (p < 0.001). Similar values of enamel F were observed for all fluoridated toothpastes (p > 0.001). Conclusion: The addition of 0.5%HMPnano to a 1100 F toothpaste significantly enhances its effects against enamel demineralization when compared to its counterpart without HMPnano in vitro. Clinical significance: Toothpaste containing 1100 ppm F associated with HMPnano has a higher potential to reduce the demineralization compared to 1100 ppm F. This toothpaste could be a viable alternative to patients at high risk of caries.
Keywords: Demineralization; Dental enamel; Nano-size; Polyphosphates; Toothpastes